Pengaruh Pengaturan Waktu Pemberian Air Minum yang Berbeda Temperatur terhadap Performan Ayam Petelur Periode Grower - Dede Risnajati (Universitas Sebelas Maret (UNS), 2011)
The purpose of this study was to investigate the effect of interaction between drinkingwater provision and drinking water temperature on performance of growing period laying hens. The research used Complete Randomized Design factorial pattern with two factors. The first factor consisted of five times of drinking water provision, ie, without restriction (WO), reduction in the provision of drinking water 2 hours (W1), 3 hours (W2), 4 hours (W3), and 5 hours per day (W4). The second factor consisted of two drinking water temperatures: 25-27 °C (T0) and 21-23 °C (T1). Each treatment was repeated 3 times and each replication consisted of five chickens. Data were analyzed with analysis of variance and continued with Duncan’s test. There was interaction between drinking water provision and drinking water temperature on body weight and feed conversion. The 2-hour reduction of drinking water provision per day with water temperature 21-23 °C produced the best performance of laying hens in growing period.Key words: laying hens, performance, grower, drinking water